The bidirectional temporal relationship between parenting stress and child maltreatment: a cross-lagged study based on intervention and cohort data - Han, Qing; Jocson, Rosanne; Kunovski, Ivo; Raleva, Marija; Juhari, Rumaya; Okop, Kufre; Oppler, Annathea; Wilson, Katherine; Cirovic, Tanja; Sacolo Gwebu, Hlengiwe; Alampay, Liane; Eagling-Peche, Stephanie; et al. (Elsevier, 2024)
Background: Parenting stress has long been proposed as a major risk factor for child maltreatment. However, there is a lack of evidence from existing studies on the temporal sequence to establish a causal relationship. This study aims to examine bidirectional temporal relationships between parenting stress and child maltreatment. Methods: Longitudinal data from two different sources were analysed: a pre-post study of an online parenting programme conducted across six countries - the ePLH Evaluation Study, and a prospective cohort study in the United States - LONGSCAN. Cross-lagged panel model on parenting stress and child maltreatment was used in each dataset. Results: Based on repeatedly measured data of 484 caregivers in the ePLH study across five time points (every two weeks), we found that parenting stress at an earlier time point predicted later child maltreatment (IRR = 1.14, 95 % CI: 1.10,1.18). In addition, the occurrence of child maltreatment was associated with higher subsequent short-term parenting stress (IRR = 1.04, 95 % CI: 1.01,1.08) and thus could form a vicious circle. In the LONGSCAN analysis with 772 caregivers who were followed up from child age of 6 to child age of 16, we also found parenting stress at an earlier time point predicted later child maltreatment (β = 0.11, 95 % CI: 0.01,0.20), but did not observe an association between child maltreatment and subsequent long-term parenting stress. Limitations: Potential information bias on the measurements. Conclusions: This study provides evidence for a bidirectional temporal relationship between parenting stress and child maltreatment, which should be considered in parenting intervention programmes.